Accuracy of self-reported drug use among offenders: findings from the Arrestee Drug Abuse Monitoring-II Program - Peters, Roger H. (Criminal justice and behavior, 2015)
The study examined data from the Arrestee Drug Abuse Monitoring-II (ADAM-II) program from 2007 until 2010 at 10 U.S. metropolitan jails to determine factors influencing the accuracy of self-reported drug use. The overall kappa coefficient for self-report data and urinalysis results of any type of drug use in the past 72 hr was .52, indicating a moderate level of agreement. Greater accuracy in self-reported drug use was found among arrestees who tested positive for methamphetamine and marijuana, although these results differed by age and race/ethnicity. African Americans provided less accurate self-reports of drug use than Caucasians, and younger arrestees less accurately self-reported all types of drug use except for marijuana. Persons with no prior arrests had higher accuracy of self-reported drug use than those with a history of frequent arrests, and prior involvement in substance abuse treatment was associated with more accurate self-reporting of drug use. Findings indicate moderate accuracy of self-reported drug use among new arrestees, with the accuracy influenced by demographic factors, arrest history, and substance abuse treatment history.